PENDAMPINGAN KEWIRAUSAHAAN DI BIDANG PENDIDIKAN BAGI MAHASISWA - ernita, mahdar; Susanty Harahap, Fatimah Depi; Sariah, Sariah (COMMUNITY SERVICE JOURNAL OF ECONOMICS EDUCATION, 2025)
Education, which is often understood as a process of self-maturation, is combined with entrepreneurship, which in French means adventurer, risk taker and entrepreneur. The location of this community service is in the city of Pekanbaru. The main targets for service are Economic Education alumni in the Pekanbaru City area. The approach used in this community service activity is Participatory Action Research (PAR). This webinar was carried out via zoom with a link. This activity was carried out in 2 sessions, the first session. Each participant took this session seriously because the material provided was very interesting and was delivered by one of the lecturers who focused on the field of business management. The second session of explanation continued with the quite technical part, namely: the technicalities of creating study guidance. In this session, private tutoring is given more detail, because this is very easy for students to execute and is the quickest to implement. And it was concluded that alumni students were interested in businesses.. Most of them were motivated and wanted to create businesses in the education sector (Edupreneur).